Nieruchomości przedsiębiorstw - nowoczesne koncepcje zarządzania - Śmietana, Katarzyna (Company Property - Modern Management Concepts, 2007)
It is a classical approach to perceive property as an object entailing costs, which contributes to facilitating the realization of certain functions connected with the statutory activity of a unit. Modern approaches indicate that property should be regarded as an object generating profit and increasing the value of the whole company. It requires a more pro-active approach on the part of the managing body and their involvement in the property management. By performing its basic activity, the subject can at the same time affects the value of the property and the value of the whole company. Modern property management concepts consider the fact that property constitutes an element in the overall process of a company's activity. What is particularly important in this context, is the effective management of resources whose value translates into the value of their related assets. The idea of facility management expresses benefits resulting from transferring the nonproductive sphere of the company activity over to specialists who, by undertaking proper actions, aim at activating property and thus contribute to its more effective usage.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 570-578